The Influence Of Social Media Influencers, Service Quality On Customer Buying Decision Through Trustworthiness On Gojek - Elsa Niarawati; Zulvia Khalid (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This Independent Research aims to analyze the influence of Social Media Influencers (X1), Service Quality (X2), and Trustworthiness (Z) on Customer Buying Decision (Y) of Gojek Customers in South Tangerang. Furthermore, instrument used in this research is questionnaire, then processed through SPSS 22.0 with several test conducted namely, data analysis, validity test, reliability test, correlation test, f-test, t-test, multiple regression analysis and hypothesis testing. Meanwhile, the amounts of participations in this study were 97 respondents using purposive sampling method with population the customer of Gojek that are living in South Tangerang. Conclusion is obtained through T Test that indicate social media influencer have significant influence on customer buying decision as partially. Service Quality have significant influence on customer buying decision as partially. Trustworthiness have significant influence on customer buying decision as partially.